Answer:
a) true
Explanation:
[P₀ x (1 - F)] = [Div₀ x (1 + g)] / (Re - g)
if g = 0
[P₀ x (1 - F)] = Div₀ / Re
cost of internal equity ⇒ {Rie x [P₀ x (1 - F)]} / Div₀, but F = 0, so (Rie x P₀) / Div₀
cost of external equity ⇒ {Ree x [P₀ x (1 - F)]} / Div₀
we must equal them:
(Rie x P₀) / Div₀ = {Ree x [P₀ x (1 - F)]} / Div₀ ⇒ Div₀s are cancelled out
Rie x P₀ = {Ree x [P₀ x (1 - F)]} ⇒ P₀s are cancelled out
Rie = Ree x (1 - F)
Ree = Rie (1 - F)
cost of external equity = cost of internal equity / (1 - F)